An annotated bibliography of materials in Thailand written and/or published in the Philippines, 1973-1981 - Kittima Pongsubjaroen (1982)
The purpose of this study is to annotate and provide a listing of materials on Thailand written and/or published in the Philippines from August 1973 to December 1981, particularly in view of the significant researches and studies in various subject areas.